Identification of the Dominant Harmonic Source Type in the Distribution Network Using the Soft Computing Technique - Sasmita Lenka; Pampa Sinha; Kaushik Paul; Chitrlekha Jena; Swagat Das; Baseem Khan (International Transactions on Electrical Energy Systems)
An innovative technique has been proposed for determining the position and characteristics of harmonic generating resources in a distribution system. The proposed methodology is primarily based on the wavelet decomposition of power signals on the factor of dimension. Detail power or harmonic power calculation at level 1 reduces the computational burden of the algorithm. The distinguishing harmonics concept can be used to detect a harmonic generating source from the distribution network. The sampling frequency is chosen so that the appropriate harmonic data are captured at level 1 and the pseudo-frequency of the wavelet decomposition at first level is close to the characteristic frequency of the load. The proposed method has been applied in different types of distribution systems to check its validity.